Myocardial Troponin T Release Is Associated with Enhanced Fibrinolysis in Patients with Acute Coronary Syndromes - Ehlers, Raila; Büttcher, Eva; Kazmaier, Silke; Beyer, Martin E.; Helber, Uwe; Szabo, Sebastian; Wendel, Hans Peter; Hoffmeister, Hans Martin (Thrombosis and Haemostasis, 2001)
Patients with acute coronary syndromes (ACS) frequently present with signs of disturbed fibrinolysis. The present study investigates the correlation of alterations in the fibrinolytic system and the amount of myocardial damage characterized by troponin release.In 85 patients with ACS markers of plasmin activation, plasminogen activator system and troponin T (TnT) were measured initially and after 48 h. Patients with TnT release (≥ 0.01 g/l) at admission had higher TPA levels than those without release (10.2 ± 0.7 ng/ml vs. 7.6 ± 0.5 ng/ml; p <0.01). Additionally, patients with positive TnT had higher D-dimer levels initially (457 ± 39 ng/ml vs. 316 ± 22 ng/ml; p < 0.01) and 48 h later (451 ± 42 ng/ml vs. 275 ± 37 ng/ml; p < 0.01). The association of myocardial damage with a prothrombotic state and an enhanced fibrinolysis may explain the high prognostic value of troponin measurements in respect to future coronary events.
Keywords: Acute coronary syndromes; fibrinolytic system; plasminogen activator system; plasmin activation; troponin T